PENGARUH UKURAN PERUSAHAAN, KOMITE AUDIT DAN LEVERAGE TERHADAP INTEGRITAS LAPORAN KEUANGAN - Kadek Emayanti; Ni Ketut Muliati (Hita Akuntansi dan Keuangan, 2020)
This study aims to obtain empirical evidence regarding the effect of company size, audit committee and leverage on the integration of financial statements in the Indonesian Stock Exchange in the period of 2014-2018. The technique for selecting sampeli in this study is purposive sampling and obtaining as many as 18 sampi with 79 observations. Techniques of data analysis in this study are techniques of analysis of linear regression. The results of the research analysis show that the firm size variable has a positive coefficient of 0.223 with a significance value of 0.013 <0.05 so that the firm size variable has a positive influence on the integration of financial statements. The audit committee committee variable has a positive coefficient of 1.568 with a significance score of 0.049 <0.05 so that the committee variable has a positive influence on the integration of the financial statements. The leverage variable has a negative coefficient value of -0.216 with a significance value of 0.273> 0.05 so that the leverage variable does not affect the financial statement integration.